Who am I? Autobiographical retrieval improves access to self-concepts. Issue 8 (13th September 2016) - Charlesworth, Lara A.; Allen, Richard J.; Havelka, Jelena; Moulin, Chris J. A.
Abstract : It is considered that an individual's current self-concept plays a crucial role in guiding the retrieval of autobiographical memory. Using a novel fluency paradigm, the present research examined whether or not the reverse is also true, that is, does memory retrieval influence the description of the conceptual self? Specifically, this study examined the effect of prior autobiographical reverie on the subsequent retrieval of stored self-concepts. Participants wrote a description of a personally relevant memory or a control topic (of no relevance to the self), following which they had 60 seconds to generate as many self-defining statements as possible, each beginning with I am . Participants engaging in autobiographical retrieval generated significantly more statements than those in the control condition, suggesting that autobiographical retrieval increased access to self-concepts. Type of statement also varied according to group. Participants in the autobiographical memory condition were more likely to conceptualise themselves in relation to their psychological traits, and this was replicated in a second experiment conducted online. Findings support the idea that self and episodic memory are highly related constructs, and are discussed in relation to implications for individuals with autobiographical memory deficits.